Navigating the complexities of anesthetic management in a preterm neonate with double outlet right ventricle posted for noncardiac surgery (Journal of Ideas in Health, 2025)
Background: Double outlet right ventricle (DORV) is an uncommon congenital heart defect characterized by the simultaneous emergence of both the aorta and pulmonary artery from the right ventricle. This condition is frequently linked with other congenital anomalies, such as imperforate anus, which presents considerable challenges for anesthesiologists. This case report outlines the effective anesthetic management of a preterm neonate diagnosed with DORV and imperforate anus, who was scheduled for an urgent sigmoid colostomy. Case presentation: A 6-day-old preterm female weighing 2.2 kg, exhibited DORV along with a subaortic ventricular septal defect, mild pulmonary stenosis, adequate biventricular function, and moderate pulmonary hypertension. Additionally, she presented with an imperforate anus accompanied by a recto-vaginal fistula. The preoperative assessment involved echocardiography, electrocardiography, and various laboratory tests. The pediatric cardiologist advised that the patient's oxygen saturation should be maintained within the range of 80-85% throughout the emergency colostomy procedure. Anesthetic management involved premedication with glycopyrrolate, ondansetron, fentanyl, and dexamethasone. The patient was induced with sevoflurane and intubated with a 2 mm endotracheal tube. Anesthesia was maintained with a mixture of air and oxygen, sevoflurane, and atracurium. Hypothermia was prevented using a warmer, and fluid management was guided by the patient's hemodynamic parameters. After the 1-hour surgery, the patient was transferred to the neonatal intensive care unit, where she was initially supported with synchronized intermittent mandatory ventilation and later extubatedConclusion: The effective anesthetic management of this preterm neonate with DORV and imperforate anus necessitated a comprehensive understanding of the associated cardiac and anorectal anomalies, meticulous preoperative planning, and a collaborative multidisciplinary approach to perioperative care. The anesthesiologist was instrumental in ensuring the patient's safety and enhancing the surgical conditions throughout the emergency colostomy procedure.
Keywords: Double Outlet Right Ventricle (DORV), Imperforated Anus, Preterm Neonate, Neonatal Emergency, Congenital Anomalies, Multidisciplinary Approach, India